Stiska zaradi neplodnosti in postopki oploditve z biomedicinsko pomočjo v globalni perspektivi - Bregar, Sandra (Socialno delo, 2015)
With global declining in fertility rates and millions of people suffering from infertility, assisted reproductive technology provides an important solution. Factors that contribute to high rates of infertility are in developed countries different than in developing countries. Developed countries are postponing childbearing and therefore facing high rates of primary infertility. Even though there is little voluntary effort to postpone childbearing in developing countries, there are high rates of secondary infertility. This is a result of sexually transmitted infections, unsafe abortion and poor maternity care (leading to infections). Cultural background has a significant impact on the extensive and long-lasting psychological and social consequences of infertility. Despite the fact that assisted reproductive technology procedures provide an important solution for the hardships of infertility, they remain too expensive or otherwise inaccessible for the majority of the world's population. Regulation, legalization and criteria of eligibility for the funding and reimbursement of reproductive technologies vary significantly across different countries. Consequently many are forced to use cross border reproductive care, which is not without danger. Global ensuring of safe, affordable and reliable assisted reproductive technology services in the 21st century is far from being realised.
Keywords: reprodukcija; reproduction; reproductive technology; reproduktivna tehnologija; rodnost; fertility; family planning; neplodnost; heath care; načrtovanje družine; zdravstvena oskrba